Radiotherapy for benign head and neck paragangliomas: A 45‐year experience. Issue 23 (24th July 2014) - Gilbo, Philip; Morris, Christopher G.; Amdur, Robert J.; Werning, John W.; Dziegielewski, Peter T.; Kirwan, Jessica; Mendenhall, William M.
<x xml:space="preserve">Abstract</x> BACKGROUND Paragangliomas of the head and neck are rare, slow‐growing, generally benign tumors of neuroendocrine cells associated with the peripheral nervous system that commonly involve the carotid body, jugular bulb, vagal ganglia, and temporal bone. Treatment options include surgery, radiotherapy (RT), stereotactic radiosurgery (SRS), and observation. This article briefly reviews our 45‐year institutional experience treating this neoplasm with RT. METHODS From January 1968 through March 2011, 131 patients with 156 benign paragangliomas of the temporal bone, carotid body, jugular bulb, or glomus vagale were treated with RT at a median dose of 45 Gy in 25 fractions. The mean and median follow‐up times were 11.5 years and 8.7 years, respectively. RESULTS Five tumors (3.2%) recurred locally after RT, all within 10 years of treatment. The overall local control rates at 5 and 10 years were 99% and 96%, respectively. The cause‐specific survival rates at 5 and 10 years were 98% and 97%, respectively. The distant‐metastasis free survival rates at 5 and 10 years were 99% and 99%, respectively. The overall survival rates at 5 and 10 years were 91% and 72%, respectively. There were no severe complications. CONCLUSION RT for benign head and neck paragangliomas is a safe and efficacious treatment associated with minimal morbidity. Surgery is reserved for patients in good health whose risk of associated morbidity is low. SRS may be suitable for patients with skull base tumors <3 cm where RT is logistically unsuitable. Observation is a reasonable option for asymptomatic patients with a limited life expectancy. Cancer 2014;120:3738–3743. © 2014 American Cancer Society.